Criminological study of child sex offenders looking at the upbringing and social dynamics of the offender - Mphatheni, Mandlenkosi Richard (International Journal of Research in Counseling and Education, 2024)
Sexual abuse of minors happens at an alarming rate, resulting in various health issues for the victims. The abuse affects children of various ages and at varying rates. Child sexual abuse is a serious social and health issue worldwide. Child sexual abuse is receiving much-needed attention from global society, and the South African government is being praised for its creative legislative frameworks aimed at addressing sexual offences against children perpetrated by adults. Nonetheless, understanding offenders' perspectives is critical in pinpointing the source of their sexual deviant behaviour. Thus, studying the formation and upbringing of child sex offenders is critical to understanding their sexual criminal conduct. The purpose of this research was to investigate how the environment influences persons who sexually assault children. The objective was to demonstrate a relationship between an individual's upbringing and sexual offences against minors. The study collected data using qualitative research technique and semi-structured interviews. Snowball and purposive selection techniques were utilised to recruit research participants from two South African correctional services. The study's participants included incarcerated sex offenders, psychologists, and social workers. The study found that several childhood traumas are to blame for the sexual offending or the behaviour of the offenders. Growing up in a hostile environment, substance abuse by both or either parent, or a lack of paternal attention are some of the early challenges. The living conditions in which a person was reared increase the chance of sexually abusing children, especially if there is family dysfunction. Neglectful parenting style has been found as a risk factor for children who grow up to commit sexual crimes against minors. Parenting style is associated with the kind of attachment a person has with their caregivers as a child. Ambivalent attachment type has been linked to child sexual offending. The study proposes that additional efforts be made to ensure that children are nurtured in a safe environment free of family violence.